Education and Coronary Heart Disease Risk: Potential Mechanisms Such as Literacy, Perceived Constraints, and Depressive Symptoms. (June 2015) - Loucks, Eric B.; Gilman, Stephen E.; Howe, Chanelle J.; Kawachi, Ichiro; Kubzansky, Laura D.; Rudd, Rima E.; Martin, Laurie T.; Nandi, Arijit; Wilhelm, Aude; Buka, Stephen L.
Objective . Education is inversely associated with coronary heart disease (CHD) risk; however the mechanisms are poorly understood. The study objectives were to evaluate the extent to which rarely measured factors (literacy, time preference, sense of control) and more commonly measured factors (income, depressive symptomatology, body mass index) in the education-CHD literature explain the associations between education and CHD risk. Method . The study sample included 346 participants, aged 38 to 47 years (59.5% women), of the New England Family Study birth cohort. Ten-year CHD risk was calculated using the validated Framingham risk algorithm that utilizes diabetes, smoking, blood pressure, total cholesterol, high-density lipoprotein cholesterol, age, and gender. Multivariable regression and mediation analyses were performed. Results . Regression analyses adjusting for age, race/ethnicity, and childhood confounders (e.g., parental socioeconomic status, intelligence) demonstrated that relative to those with greater than or equal to college education, men and women with less than high school had 73.7% (95% confidence interval [CI; 29.5, 133.0]) and 48.2% (95% CI [17.5, 86.8]) higher 10-year CHD risk, respectively. Mediation analyses demonstrated significant indirect effects for reading comprehension in women (7.2%; 95% CI [0.7, 19.4]) and men (7.2%; 95% CI [0.8, 19.1]), and depressive symptoms (11.8%; 95% CI [2.5, 26.6]) and perceived constraint (6.7%, 95% CI [0.7, 19.1]) in women. Conclusions . Evidence suggested that reading comprehension in women and men, and depressive symptoms and perceived constraint in women, may mediate some of the association between education and CHD risk. If these mediated effects are interpreted causally, interventions targeting reading, depressive symptoms, and perceived constraint could reduce educational inequalities in CHD.